Discovering nutrition [ - Carr, Timothy P. (Blackwell Publications, 2003)
Discovering Nutrition offers a concise look at the science of nutrition through the lens of today's issues and hot topics. In this compact, accessible overview, the central topics and scientific building blocks of nutrition are emphasized. The book follows the "life and times" of nutrients from their presence in the environment and the body to their role in health and disease, with a focus throughout on the current practical and social issues.:.; Brief chapter overviews.; Essential Background and Key Points at the beginning of each chapter.; Descriptions of current dietary guidelines